READING THROUGH THE GENDER AND REGIONAL IMAGES: A STUDY OF SELECT FOOD MEMOIRS FROM INDIA - Mohan, Revathy S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food is an endlessly interpretable artifact and so the flux keeps food studies as an ever-dynamic discipline. Culinary memoirs reflect the life experiences of an individual as well as a community. Food and language bridge the gap between nature and culture. They become social constructs that can create and distort our identity. Language and food have become powerful media that can manipulate and influence the human mind invariably. It is significant to understand the role food plays in reasserting societal norms as an indispensable cultural icon of our everyday lives and the immense potential it has to transmute our perspective seamlessly. This paper is an attempt to explore the gender and regional stereotypes in select illustrated culinary memoirs, Travels through South Indian Kitchen by Nao Saito and Aparna Jain’s The Sood Family Cookbook. These works reflect how food explains the deeply embedded structures of gender and region in our everyday lives. Close analyses of these texts especially that of the verbal and non-verbal language show that food acts as a tool in distorting as well as reaffirming certain stereotypes prevalent in our society.